Eating distractions as predictors of ultra-processed food consumption and Mediterranean diet adherence in adolescents - José Francisco López-Gil; Fiorella Quiroz-Cárdenas; José Adrián Montenegro-Espinosa; Emily Cisneros-Vásquez; Camila Miño; Mónica Elizabeth Castillo-Miñaca; Rubén Alejandro Unda-López; Lina América Sánchez-Charcopa; María Paula Zalamea-Delgado; Martina Jared Masache-Cruz; David Alejandro Palacios-Zavala; Mateo Alejandro Barriga-Collantes; et al. (Scientific Reports)
Abstract Previous studies have examined the relationships between some eating distractions and diet quality in the young population. However, to our knowledge, no study has analyzed the associations between multiple eating distractions (e.g., using a mobile phone, watching television [TV], eating while standing) and diet quality, particularly in terms of ultra-processed food (UPF) consumption and adherence to the Mediterranean diet (MedDiet) among adolescents. The objective of the current study was to analyze the relationships of eating distractions with UPF consumption and adherence to the MedDiet in a sample of Spanish adolescents. This cross-sectional study used data from 826 adolescents aged 12–17 years from the Eating Healthy and Daily Life Activities study in Spain. The following eating distractions were assessed via a self-report questionnaire: “(1) eating while talking on the phone/sending short message service [SMS]/emails or using social networks”, (2) watching TV while dinner, and (3) eating while standing”. The Mediterranean Diet Quality Index for children and adolescents (KIDMED) was utilized to evaluate adherence to the MedDiet. A self-administered food frequency questionnaire, previously validated for the Spanish population, was used to assess UPF consumption. The associations of eating distractions with UPF consumption and MedDiet adherence were analyzed via generalized linear models. The models were adjusted for sex, age, socioeconomic status, body mass index, physical activity, sedentary behavior, and sleep duration. A significant association was found, with a higher eating distraction score corresponding to greater UPF consumption (unstandardized beta coefficient [B] = 71.25; 95% confidence interval [CI] 34.69–107.82; p < 0.001). Furthermore, a higher eating distraction score was associated with a lower KIDMED score (B − 0.29; 95% CI − 0.39 to − 0.18; p < 0.001). Individually, for grams of UPFs consumed, a significant association was observed for eating while using a phone or social network, which was linked to higher UPF consumption (B = 120.70; 95% CI 57.83–183.57; p < 0.001). However, the associations for eating while watching TV (B = 49.60; 95% CI − 9.01 to 108.21; p = 0.098) and eating while standing (B = 63.66; 95% CI − 37.92 to 165.25; p = 0.220) did not reach statistical significance. For KIDMED score, all the eating distractions were associated with a significant decrease, with the largest effect observed for phone or social network use (B = − 0.44; 95% CI − 0.62 to − 0.26). Watching TV (B = − 0.18; 95% CI − 0.35 to − 0.01; p = 0.037) and eating while standing (B = − 0.42; 95% CI − 0.71 to − 0.13; p = 0.004) also showed significant negative associations. Although diet quality is influenced by multiple factors, eating distractions may negatively impact adolescents by increasing UPF consumption and reducing adherence to the MedDiet. These findings underscore the importance of understanding the role of the eating environment in shaping healthy dietary habits.